2020
DOI: 10.3389/fmicb.2020.576520
|View full text |Cite|
|
Sign up to set email alerts
|

High Representation of Archaea Across All Depths in Oxic and Low-pH Sediment Layers Underlying an Acidic Stream

Abstract: Parys Mountain or Mynydd Parys (Isle of Anglesey, United Kingdom) is a mine-impacted environment, which accommodates a variety of acidophilic organisms. Our previous research of water and sediments from one of the surface acidic streams showed a high proportion of archaea in the total microbial community. To understand the spatial distribution of archaea, we sampled cores (0–20 cm) of sediment and conducted chemical analyses and taxonomic profiling of microbiomes using 16S rRNA gene amplicon sequencing in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
(103 reference statements)
2
19
0
Order By: Relevance
“…For example, Thermoplasmatales dominates AMD from Dabaoshan Mine (Guangdong Province, China) (Lu et al, 2010). Distaso et al (2020) and Korzhenkov et al (2019) also recently reported higher representation of archaea Thermoplasmatales across all depths in oxic and low-pH sediment layers underlying an acidic stream in Parys Mountain (Mynydd Parys) AMD habitat in the UK, indicating contribution of these organisms to carbon, and probably to iron and sulfur cycles in this ecosystem. Gupta et al (2021) also reported the dominant archaeal communities in AMD sediment of Malanjkhand Copper Project, India as Thermoplasmata, Nitrososphaeria, Bathyarchaeia, Hydrothermarchaeota, Methanomassiliicoccales, Methanobacteriaceae, Methanocellaceae, Haloferaceae, Methanosaetaceae, and Methanoregulaceae.…”
Section: Microbial Community Diversity Under Amd Habitatsmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, Thermoplasmatales dominates AMD from Dabaoshan Mine (Guangdong Province, China) (Lu et al, 2010). Distaso et al (2020) and Korzhenkov et al (2019) also recently reported higher representation of archaea Thermoplasmatales across all depths in oxic and low-pH sediment layers underlying an acidic stream in Parys Mountain (Mynydd Parys) AMD habitat in the UK, indicating contribution of these organisms to carbon, and probably to iron and sulfur cycles in this ecosystem. Gupta et al (2021) also reported the dominant archaeal communities in AMD sediment of Malanjkhand Copper Project, India as Thermoplasmata, Nitrososphaeria, Bathyarchaeia, Hydrothermarchaeota, Methanomassiliicoccales, Methanobacteriaceae, Methanocellaceae, Haloferaceae, Methanosaetaceae, and Methanoregulaceae.…”
Section: Microbial Community Diversity Under Amd Habitatsmentioning
confidence: 90%
“…According to Edwards et al (2000), about 75% of AMD produced results from microbial activity. Under the extremophilic AMD environment, acidophilic microbial communities belonging to Bacteria, Archaea, and Eukarya domains dominates, with members of phylum Proteobacteria, Nitrospira, Actinobacteria, Firmicutes, and Acidobacteria being the dominant bacterial taxa (Mesa et al, 2017;Lukhele et al, 2019;Distaso et al, 2020), as well as iron/sulfur-oxidizing microbes such Leptospirillum ferrooxidans, Ferrovum, Acidothiobacillus occurring in an environmentally dependent biogeographic pattern (Kuang et al, 2013(Kuang et al, , 2016Wang et al, 2019b). In addition, a large number of rare taxa constituting a "rare biosphere" in the microbial community that may perform crucial function in AMD ecosystems have been reported (Luo et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Acid mine drainage is an extreme acid environment and low pH will threaten the growth of microorganisms ( Rothschild and Mancinelli, 2001 ; Huang et al, 2016 ; Distaso et al, 2020 ). In order to adapt to acid stress, microorganisms will form a series of defense mechanisms to regulate intracellular pH, K + , and Na + concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The purified barcoded amplicons were quantified by Qubit™ dsDNA BR Assay Kit (Life Technologies, USA), pooled in equimolar amounts and sequenced on Illumina MiSeq™ platform (Illumina Inc., San Diego, CA, USA) using paired-end 250 bp reads at the Centre for Environmental Biotechnology (Bangor, UK). Sequencing reads were processed and analysed as previously described (38). All statistical analysis was conducted using R programming environment (39) prcomp function and in-house scripts for graphical design.…”
Section: Methodsmentioning
confidence: 99%